17α-Hydroxyprogesterone Caproate Inhibits Cytokine Production via Suppression of NF-κB Activation - Hu, Tao; Tang, Chengjifu; Stern, Sydney; Yang, Luan; Du, Tom (Frontiers in Pharmacology, 2022)
Cytokine release syndrome (CRS) is one of the leading causes of morbidity and mortality in COVID-19 patients with elevated levels of circulating cytokines contributing to various clinical symptoms. Favorable control of CRS represents a promising and effective strategy to mitigate the clinical outcomes of hospitalized patients with moderate to severe pneumonia. Using in vivo cytokine release assay in human peripheral blood mononuclear cell (PBMC)-engrafted immunodeficient mice, we reported that 17α-hydroxyprogesterone caproate (17-OHPC), a synthetic progestogen, exhibited significant inhibition of OKT-3-stimulated production of numerous cytokines including TNF-α, IFN-γ, IL-2, IL-4, IL-6, IL-10, and GM-CSF. Furthermore, 17-OHPC inhibited in vitro production of IFN-γ, IL-1β, IL-2, IL-6, and IL-10 in human PBMCs stimulated with OKT3, while exhibiting down-regulation of the mRNA levels of TNF-α, IFN-γ, IL-2, IL-6, and IL-10. Using the same human PBMCs, additional stimulators anti-CD28 antibody or PHA treatments led to substantial cytokine production, which was also attenuated by 17-OHPC. OKT3-stimulated phosphorylation of IκBα and nuclear translocation of NF-κB p65 in human PBMCs were also reversed by 17-OHPC, suggesting its inhibition on NF-κB signaling in immune cells. Taken together, this work reported both in vivo and in vitro inhibition of cytokine production by 17-OHPC, presumably by virtue of its suppression of NF-κB signaling. These findings provide pharmacological evidence to support the potential application of 17-OHPC in treating CRS associated with COVID-19.